Answer:
We conclude that:
f(g(3)) = 2
Hence, option B is correct.
Explanation:
Given the f(x) table
x 2 3 4 5
f(x) 0 1 2 3
Given the g(x) table
x 1 2 3 4
g(x) 1 2 4 8
We need to determine f(g(3)).
In order to determine f(g(3)), first, we need to determine g(3)
It is clear from the table of g(x),
at x = 3, g(3) = 4
so
f(g(3)) = f(4)
Now, we need to check the value of f(4) at x = 4 using the table f(x)
It is clear from the table of f(x),
at x = 4, f(4) = 2
Thus,
f(g(3)) = f(4) = 2
Therefore, we conclude that:
f(g(3)) = 2
Hence, option B is correct.